(untitled) (Window of Public Health Journal, 2026)
Pneumonia is an acute respiratory infection that attacks the lungs. The lungs consist of small sacs called alveoli, which fill with air when a healthy person breathes. This study aims to determine the factors associated with pneumonia incidence among toddlers at the Makassar Class II Pneumonia Hospital. The research design is quantitative and cross-sectional. The study population consisted of 96 respondents. The sample calculation used the Lemešow formula, yielding a sample of 77 respondents. The instrument used was a questionnaire. Data analysis used univariate and bivariate analysis. The analyzed data are presented in tabular form, followed by a narrative explanation. The results of the study showed that there was a relationship between nutritional status and the incidence of pneumonia in toddlers, namely (p = 0.000 <0.05), there was a relationship between LBW and the incidence of pneumonia in toddlers, namely (p = 0.004 <0.05), there was no relationship between immunization status and the incidence of pneumonia in toddlers, namely (p = 0.083 <0.05), there was a relationship between exclusive breastfeeding and the incidence of pneumonia in toddlers, namely (p = 0.040 <0.05), there was a relationship between the provision of vitamin A and the incidence of pneumonia in toddlers, namely (p = 0.007 <0.05), there was a relationship between smoking behavior of family members and the incidence of pneumonia in toddlers, namely (p = 0.036 <0.05), there was a relationship between the use of mosquito repellent and the incidence of pneumonia in toddlers, namely (p = 0.028 <0.05). It is hoped that parents/caregivers of toddlers will pay more attention to the risk factors for pneumonia.